Métodos de formação de preço de venda em sistemas ERP por intermédio de arquitetura orientada à serviços do framework FrameMK - Mazer Junior, Ademir (2013)
The sales price definition process is critical for competitive success of organizations. The lack of free ERP systems that implement several pricing methods create a context when managers need of tools that assist then in this task. The Research Group on Information Systems at Federal Technological University of Parana, Campus Ponta Grossa, is developing an application called FrameMK (Framework for Sales Price Definition). Thus, this work has as it’s main goal to demonstrate the use of various pricing methods, through the framework for sale price definition - FrameMK, in free ERP systems, through a service oriented architecture layer. Tools were used and methods of software development to achieve the goal, including UML modeling language and the Java programming language . The stages performed started with the study of the framework followed by the implementation of direct exposure services of pricing methods implemented. From this point there was the description of the service requirements and high-level features that assisted in the implementation stage of the Web services using the technologies SOAP / WSDL and REST. Therefore, the main results were: design models of the three levels of service. Models for deployment FrameMK and use cases as the basis for the description of requirements for the functions development of the third level services. The software product that implements the service classes resulting in a service-oriented architecture for FrameMK, sets of unit testing code and its deployment on the servers of the Research Group on Information Systems at Federal Technological University of Parana, Campus Ponta Grossa.